More than Just Type 1 or Type 2: Radiologically and Anatomically Refined Lunate Classification Correlating Ulnar Carpal Alignment and Hamate-Lunate Osteoarthrosis - Wolfram Demmer; Lia K. Fialka; Jens Waschke; Irene Mesas Aranda; Elisabeth Haas-Lützenberger; Riccardo Giunta; Paul Reidler (Journal of Functional Morphology and Kinesiology, 2025)
Background: Hamate-lunate impingement or osteoarthritis can be a cause of ulnar-sided wrist pain. In the literature, the lunate has commonly been classified according to the configuration of its distal articular surface into type 1 and type 2, as described by Viegas. A type 1 lunate possesses only a distal articular surface for the capitate, while a type 2 lunate shows an additional medial facet articulating directly with the hamate. Type 2 lunates have been identified as a risk factor for ulnar-sided wrist pain and the development of osteoarthritis in the midcarpal wrist. However, this does not sufficiently explain all arthritic changes between the hamate and lunate. Methods: In this prospective anatomical-radiological cadaver study, 60 wrists were examined. The midcarpal articulation was documented using conventional X-ray, CT arthrography, and anatomical dissection. The study specifically analyzed the positioning of the lunate relative to the hamate apex and its association with the development of hamate-lunate osteoarthritis. For this purpose, the classification by Viegas was refined. Based on posterior-anterior (p.a.) X-ray examinations of the wrist lunates were divided into type 1a, type 1b, and type 2. The type 1a lunate articulates only with the capitate in the midcarpal joint. The type 1b lunate also articulates only with the capitate; however, medially, the apex of the hamate protrudes beyond a Differentiation Line (D-line), which extends from the radial border of the trapezium or the ulnar border of the lunotriquetral (LT) space, without forming a facet with the lunate. A type 2 lunate articulates distally with the capitate and has an additional medial facet with the hamate. Results: Osteoarthritis between the hamate and lunate was observed in both Viegas type 1 and type 2 lunates. According to our refined lunate classification, both in situ and radiologically, type 1b and type 2 lunates showed a substantially higher prevalence and severity of hamate-lunate osteoarthritis compared to type 1a lunates. However, there was no significant difference in the prevalence of hamate-lunate osteoarthritis between type 1b and type 2 lunates. Conclusions: Assessing lunate type and signs of osteoarthritis is essential when evaluating patients with ulnar-sided wrist pain. Our study demonstrates that osteoarthritis in Viegas type 1 lunate is influenced by the position of the hamate apex relative to the D-line. The refined lunate classification, based on correlated radiological and anatomical studies of the wrist, provides a straightforward method for identifying a potential cause of ulnar-sided wrist pain on p.a. X-rays. This classification can help guide further diagnostic and therapeutic decisions, such as wrist arthroscopy with possible resection of the hamate apex.